Medical and non-medical factors associated with stunting in infants and toddlers aged 3-59 months in Palembang - Elsi, Yuanita Rimadini; Fauzi, Moretta Damayanti; Anzar, Julius; Indra, Raden Muhammad; Yosy, Deny Salverra; Saputra, Indra; Ramadanti, Afifa (Indonesian Pediatric Society, 2025)
Background Although the prevalence of stunting in South Sumatera is estimated to be relatively high, there have been few studies to date on stunting and the factors associated with it in the region. Objective To determine the proportion of stunting in infants and toddlers aged 3-59 months at Mohammad Hoesin General Hospital (RSMH), Palembang, South Sumatera, and to identify medical and non-medical factors associated with stunting in these children. Methods A cross-sectional study was conducted at RSMH from April to September 2023. Stunting was defined according to the WHO standard and combined with a growth pattern that reflects chronic malnutrition. We recorded the proportion of stunting as well as data on several potential medical and non-medical risk factors of stunting. Results A total of 183 subjects met the inclusion criteria. The overall proportion of stunting was 65/183 (35.5%). The proportion of stunting was higher in boys (39.6%) and in children <2 years of age (38.2%). Medical risk factors significantly associated with stunting were infectious disease [OR 4.13 (95%CI 1.91 to 8.94); P=0.001] and chronic disease [OR 3.02 (95%CI 1.56 to 5.85); P=0.001]. The only non-medical factor significantly associated with stunting was low paternal education level [OR 2.45 (95%CI 1.17 to 5.15); P=0.016]. Conclusion During the study period, over a third of pediatric patients at RSMH experienced stunting. Infectious disease, chronic disease, and low paternal education level were significant risk factors that contributed to the occurrence of stunting.